Pengaruh Literasi Kesehatan Mental terhadap Psikologis Karyawan di PT D’ands Anugerah Sejahtera (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2025)
Mental health literacy is essential to maintaining employee productivity, health, and happiness in the work environment. The purpose of this study is to determinethe level of workers' knowledge about mental health and the elements that affect it. This research makes use of a quantitative method by conducting a survey of 35 employees of PT D'ands Anugerah Sejahtera. Data was gathered using testing the validity and credibility of the questionnaire, which was then analyzed using simple linear regression with the help of SPSS statistical software. All questionnaire items were found to be valid (r count > 0.334) and reliable (Cronbach’s Alpha > 0.6). The results of the simple linear regression analysis show that mental health literacy has a major impact on readiness to face psychological disorders, with a regression coefficient of 0.932 and a significance value of 0.000 (p < 0.05). These findings indicate that improving employees’ mental health literacy can enhance their readiness in order to manage psychological stress at work.